Perbedaan Dan Persamaan Toleransi Beragama di Rumah Susun Cipta Menanggal Blok 65 Surabaya Dengan Desa Balun Kecamatan Turi Kabupaten Lamongan: Sebuah Kajian Historis - Bernadetta Budi Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
As a country with different religious backgrounds, this diversity is one of the important advantages in building social harmony and diversity. The value of religious tolerance is also reflected in government policies that prioritize the protection of religious freedom and prohibit discrimination based on religious belief. The importance of religious tolerance in Indonesian society is also reflected in the efforts of the government, non-governmental organizations, and religious communities to encourage interfaith dialogue, strengthen comprehensive religious education, and support interfaith social activities. Through this initiative, Indonesians can raise awareness of the importance of religious tolerance and build a solid foundation for inter-religious harmony. This can be seen from the people in the Cipta Menanggal Block 65 Surabaya environment and the people of Balun Village, Turi, Lamongan. Although the two communities have differences, they have similarities in tolerance, both tribal tolerance and religious tolerance. In addition, celebrations and commemorations of religious days and have similarities in accepting mixed marriages among the younger generation. There is still mutual respect as human beings, as well as religious people